1999
DOI: 10.1271/bbb.63.884
|View full text |Cite
|
Sign up to set email alerts
|

Assembly ofStaphylococcus aureusLeukocidin into a Pore-Forming Ring-Shaped Oligomer on Human Polymorphonuclear Leukocytes and Rabbit Erythrocytes

Abstract: Staphylococcal leukecidin consists of two separate proteins, LukS and LukF, which eooperatively lyse hllman a"d rabbit pelymorphenuclear leukocytes and rabbit erythrecytes. Here we studied the pore-forming properties of leukocidin alld the melecular architecture of the leukocidin pere. (1) Leukocidin caused an eMux of potassium iens from rabbit erythrocytes and swelling of the cells before hemolysis. However, ultimate lysis of the toxin-treated swollen erythrocytes did not occur when pelyethylene glycels with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
38
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 18 publications
5
38
1
Order By: Relevance
“…This agreed well with several previous reports showing that the pore of bicomponent β-PFTs prepared on cells consisted of four molecules of each of the F and S components (22)(23)(24)(25). In contrast, several reports indicated that γHL pores formed on the erythrocyte membrane are mainly composed of six (17,26) or seven protomers (12,20,34). However, there is considerable steric constraint in the heptameric γHL model constructed by superposing individual protomers onto heptameric αHL.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This agreed well with several previous reports showing that the pore of bicomponent β-PFTs prepared on cells consisted of four molecules of each of the F and S components (22)(23)(24)(25). In contrast, several reports indicated that γHL pores formed on the erythrocyte membrane are mainly composed of six (17,26) or seven protomers (12,20,34). However, there is considerable steric constraint in the heptameric γHL model constructed by superposing individual protomers onto heptameric αHL.…”
Section: Discussionsupporting
confidence: 92%
“…Several reports using LUK pores formed on rabbit erythrocytes also demonstrated the existence of an octamer consisting of 4-plus-4 subunits (23)(24)(25). However, hexamer was also proposed based on structure modeling using monomeric structures of PVL (17) and electron microscopy of LUK pores on leukocytes and erythrocytes (26). It is also important to determine the significance of using two components.…”
mentioning
confidence: 99%
“…LukAB specifically targets phagocytes such as polymorphonuclear cells (PMNs or neutrophils) (9)(10)(11)(12), which are an integral part of the host innate immune response to S. aureus (13). The capacity to kill PMNs is conserved among all leukocidins (4,5), although the actions of LukED (14) and Hlg (15) are not limited to phagocytes (5). Despite their common cellular target, the leukocidins diverge in their potency toward PMNs of different species.…”
mentioning
confidence: 99%
“…One of the toxins, Panton-Valentine leukocidin (PVL) is associated with human pyogenic necrotizing skin infections such as furuncles, cellulitis, and abscesses, and more severe septic infections such as osteomyelitis, bacteremia, purpura fulminans, and necrotizing pneumonia (1)(2)(3)(4)(5)(6)(7)(8). PVL with γ-hemolysins (HlgA/HlgB and HlgC/ HlgB) and LukE/LukD belongs to the bicomponent pore-forming leukotoxin family (9)(10)(11)(12)(13)(14), which are thought to contribute to virulence in various infection models (15)(16)(17)(18), although some groups disagree (19,20). A class S and class F component interact sequentially and synergistically, inducing the activation and permeabilization of target cells and leading to their lysis.…”
mentioning
confidence: 99%